Implementasi Kebijakan Dinas Pariwisata dan Kebudayaan Dalam Pengembangan Objek Wisata di Pulau Kumo (Suatu Studi di Kecamatan Tobelo Kabupaten Halmaera Utara) - Lahamadi, Feki; Ogotan, Martha; Londa, Very (Sam Ratulangi University, 2016)
ABSTRACT : Kumo beach is one of the busiest beaches in North Halmahera, Kumo beach is alsoone of the island cluster of islands in front of Tobelo town which can be reached Â± 5 minutes bymotorized boat. Island Kumo is located right in front of Tobelo town with a beach shaded by treesand a beautiful white sand and the sea is clear, strong and strong and suitable for activities such assnorkeling, boating and others, the choice of the local tourists because of its beautiful sceneryaccess close from Tobelo town. Unfortunately, all the advantages of a tourist beach Kumo untappedand managed properly, it is very necessary for the implementation of policies that seriously bypolicymakers and implementers alike.The research was analyzed using qualitative descriptive method. Thus, the details can bedrawn that the data analysis technique that is performed is after the data are collected, then thenext data will be combined, depicted in narrative form sentences by providing interpretation orinterpretation based on direct observation conducted by researchers with samples of the objectexisting research or respondent which exists. The results of this research show that the efforts madeby the Department of Tourism and culture of North Halmahera District has not been able to exploreand manage the attraction beach Kumo well because they said there are various factors that hamperpolicy makers and implementers in implementing the policy of tourism development on the islandof Kumo.Keywords: Policy Implementation, Development, Attractions.